Catastrophic Health Expenditure And Multidimensional Household Poverty In Java Island, Indonesia - Ista Aryogi; Ni Made Sukartini (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to analyze the influence of household catastrophic health expenditure incidents and household characteristics on household multidimensional poverty status in Java Island, Indonesia. The study was conducted quantitatively inferentially based on IFLS 5 data in 2014 obtained from Susenas totaling 8,458 households. The data analysis used logistic regression with ordered logit model. The results of the study revealed that households experiencing catastrophic health expenditure increasingly tend to experience multidimensional poverty. Household characteristics such as the number of family members and the number of toddlers that are getting bigger can also increase this tendency. However, it is different from the level of education and location of residence which can reduce the tendency of households to experience multidimensional poverty.